PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PEMBELAJARAN BERBASIS E-LEARNING PADA SISWA KELAS XI IPA - Azizah Mujahidah Annisa (Hipotenusa Journal of Research Mathematics Education (HJRME), 2018)
This research is a classroom action research, which purpose to improve the result of the students math process of the students xi ipa by interest based learning. The research subjects were 23 students of Second Year students of SMA in Pangkajene of the second semester of academic year 2012/2013. This research was conducted in two cycles. The procedure conducted in 4 stages, called: (1) Planning, (2) Implementation of action, (3) observation, and (4) Reflection. The data collection was done by giving the cycle test I then cycle test II, and questionnaire response of students after given teaching by interest based learning. The collected data were analyzed by quantitative and qualitative. The result of this research shown that quatitatively, the result of students math learning was increase by Interest based learning. At the first cycle, the numbers of students who passed the study were 19 students (82, 6 %) with an average score of 71,00 from the ideal score of 100 that categorized high score. At the second cycle, the numbers of students who passed the study were 23 students (100 %) with an average score of 87,57 that categorized very high score. While qualitatively,during the learning process, shown that there was better of behavior change, it can be seen by the increasing of students development activity that was suitable with learning of the first and the second cycle. The students also gave positive response of learning which was seen by response questionnaire of students.